Primary Palliative: Advance Care Planning - Molina, Chanita (My University, 2017)
The lack of advance care planning has led to patients being on care plans not chosen by them, prolonged hospitalizations, increased health care costs, and prolongation of suffering with medical futility. It is important that primary care providers have the knowledge and confidence to conduct health care preference discussions with their patients prior to crisis. The purpose of this project is to determine if an educational intervention provided to primary care clinicians on advance care planning for the geriatric population with multiple chronic illnesses would prompt goals of care discussions and completion of Medical Orders for Scope of Treatment (MOST) for patients in an outpatient setting.
Keywords: Primary Care Palliative Advance Care Planning MOST forms